False Seedbed and Stale Seedbed Against Important Broadleaf Weeds: A Case Study and a Step Closer to Agroecology - Panagiotis Kanatas; Ioannis Gazoulis; Dimitra Petraki; Metaxia Kokkini; Nikolaos Antonopoulos; Ilias Travlos (Plants)
Wheat production can be reduced due to competition from weeds, with farmers relying almost exclusively on chemical solutions. However, there are alternative farming practices available. Therefore, in a field trial in Greece, we assessed the efficacy of false and stale seedbed against important broadleaf weed species and their impact on grain yield parameters. Our study determined that false seedbed resulted in a decrease in the density and biomass of broadleaf weed species like catchweed bedstraw (Galium aparine L.) up to 75% and 69% compared with the untreated control (normal seedbed preparation), respectively. The efficacy of false seedbed was higher when combined with post-emergence chemical control. Stale seedbed also resulted in adequate weed control, with a biomass reduction of up to 81%, and grain yield increased by 30% compared with the normal seedbed preparation without any herbicide use. Our results highlight the differences in the response between the weed species and also emphasize the potential of adding an alternative farming practice (like false and stale seedbed) as part of an integrated farming strategy for a sustainable and agroecological crop and weed management. In order to validate the trends observed in this case study, further field-to-field or year-to-year replication is required.